KELAYAKAN TEORITIS MEDIA PEMBELAJARAN MULTIMEDIA INTERAKTIF MATERI MUTASI UNTUK SMA - Amrulloh, Rizqi (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Abstract – This research aims to produce the learningmedia of interactive multimedia in the topic of mutationwhich is feasible theoretically. The theoretical feasibility ofinteractive multimedia consists of the feasibility of topic andmedia. The feasibility of topic consists of the suitability ofthe media content with the topic of mutation and thesuitability of the media content with learning objectives.Meanwhile, the feasibility of media consists of the format ofmedia, quality of media, and the suitability of media withthe concept. This development research used ASSUREmodel which consists of six phases. The feasibility of topicgot percentage about 89.90% and very feasible, the mediafeasibility got percentage about 84.08% and very feasible.These results show that the learning media of interactivemultimedia in the topic of mutation is feasible theoretically.Keywords: Interactive multimedia on mutation, Theoreticalfeasibility